Navigating Remedial Dhikr and Surah Memorization: A Quest for Improvement or Procedural Challenges? - Surawardi,; Hamdi, Saibatul; Maulidi, Ahmad Riyadh (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
This study explores a new phenomenon in the implementation of remedial practices that differ from the common remedial approaches. In this context, remedial activities involve reciting dhikr (remembrance of God) and memorizing short surahs (chapters) during the learning process. The research aims to describe the implementation of this remedial approach and the underlying reasons for its adoption at MA Sabilal Muhtadin. The research employs a qualitative approach using phenomenological methods. The study subjects include two teachers and five relevant informants. The research findings reveal several key points. First, the remedial activities involve two teachers but do not appear to represent the appropriate instruments for enhancing the quality of students' learning. Students are only given additional tasks, such as memorization, without receiving guidance related to unfinished learning indicators. Second, the implementation of these remedial activities arises from teachers' perceptions of limited time allocation, prompting them to take the initiative to carry out remedial practices that can be completed quickly. Teachers also believe that remedial activities can compensate for students' inadequate grades. These findings indicate that teachers possess limited knowledge about the correct procedures for remedial practices. Third, the execution of remedial activities does not align with the proper remedial procedures, resulting in minimal impact on students' improved understanding and, in some cases, an additional learning burden. The implications of this research include providing recommendations to the relevant madrasah to improve their remedial programs. These recommendations encompass practical steps, such as organizing training sessions for madrasah teachers to enhance their understanding of the correct remedial procedures.